2011
DOI: 10.1016/j.qref.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Geographic deregulation and commercial bank performance in U.S. state banking markets

Abstract: This paper examines the effects of geographical deregulation on commercial bank performance across states. We reach some general conclusions. First, the process of deregulation on an intrastate and interstate basis generally improves bank profitability and performance. Second, the macroeconomic variables -the unemployment rate and real personal income per capita -and the average interest rate affect bank performance as much, or more, than the process of deregulation. Finally, while deregulation toward full int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Many researchers study the wealth effects or accounting performance of banks after specific legislation. For example, Zou, Miller, and Malamud () use state‐level data and find both net interest margins and ROA increased during and after passage of the Interstate Banking and Branching Efficiency Act (IBBEA). Their results are an extension of Nippani and Green () who find that univariate ROA is higher after the passage of the IBBEA, but in multivariate regressions ROA is generally not significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many researchers study the wealth effects or accounting performance of banks after specific legislation. For example, Zou, Miller, and Malamud () use state‐level data and find both net interest margins and ROA increased during and after passage of the Interstate Banking and Branching Efficiency Act (IBBEA). Their results are an extension of Nippani and Green () who find that univariate ROA is higher after the passage of the IBBEA, but in multivariate regressions ROA is generally not significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Seale (2004) considered the relationship between a financial institution's branch numbers and several financial ratios, reporting that extensive branch networks are generally associated with higher noninterest income, lower interest and non-interest expenses, and higher return on equity (ROE), especially among community banks. Zou et al (2011) examined the effects of geographical deregulation on bank performances and demonstrated that profits and net-interest-margin ratios are higher for banks with a greater number of branches. Kondo (2015) investigated whether Japanese regional banks entering the banking market in other prefectures can increase their lending-based income and concluded that management-area extensions have positive effects on their lending-based income 5 ; however, they could not improve their overall profitability, i.e., return on assets (ROA) and…”
Section: Literature Reviewmentioning
confidence: 99%
“…They showed that performances improved in the post-IBBEA period; however, when controlled for real GDP and prime rate, no significant effects of IBBEA were observed. Zou et al (2011) demonstrated that the effects of the deregulation of interstate bank branching on bank performances differed according to bank size.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a recent study, Zou, Miller and Malamud (2011) examine the effects of geographical deregulation on commercial bank performance across states. They reach several conclusions.…”
Section: Introductionmentioning
confidence: 99%